The Prophylactic Effect of Single vs. Dual Antibiotic-Loaded Bone Cement against Periprosthetic Joint Infection Following Hip Arthroplasty for Femoral Neck Fracture: An Analysis of the German Arthroplasty Registry - Dominik Szymski; Nike Walter; Paula Krull; Oliver Melsheimer; Siegmund Lang; Alexander Grimberg; Volker Alt; Arnd Steinbrück; Markus Rupp (MDPI AG, 2023)
Background: Antibiotic-loaded bone cement in arthroplasties is currently experiencing increased usage. Therefore, single and double antibiotic-loaded bone cements are commercially available and used in orthopedic surgery. The aim of this investigation was to compare the clinical use of single compared to dual antibiotic-loaded bone cement for implant fixation after femoral neck fracture. Further infection rates were to be compared in (partial) arthroplasty for the treatment of femoral neck fracture for both treatment options. Methods: On the basis of the German Arthroplasty Registry (EPRD), all cases of femoral neck fracture treated with hemiarthroplasty (HA), or total hip arthroplasty (THA) with single and dual antibiotic-loaded bone cement, were included into the data analysis. The infection risk was compared using Kaplan-Meier estimates. Results: In total, 26,845 cases (HA 76.3%-THA: 23.7%) with femoral neck fracture were included. Within recent years, an increasing usage of dual antibiotic-loaded cement in Germany, with a current proportion of 7.30% in arthroplasty procedures for femoral neck fracture treatment, has been observed. In patients treated with HA, the proportion of dual antibiotic-loaded cement was 7.86%, while in those treated with THA, 5.46% of all prostheses were fixated with a two antibiotic component cement. For all arthroplasty procedures using single antibiotic-loaded bone cement after six months 1.8%, after one year 1.9%, and after five years 2.3%, of the cases failed due to periprosthetic joint infection (PJI), while in the same time period, in cases with dual antibiotic-loaded bone cement 1.5%, 1.5% and 1.5% suffered from infection (p = 0.34). A infection rate of 1.1% after HA with dual antibiotic-loaded bone cement was reported, compared to a 2.1% infection rate whilst using single antibiotic-loaded bone cement after five years (p = 0.098). The number required for treatment when using HA was 91. Conclusions: The use of dual antibiotic-loaded bone cement is increasingly used in arthroplasty procedures after femoral neck fractures. It demonstrates a reduction of PJI after HA and seems, therefore, to be a useful method for the prevention of infection, especially in patients with increased risk factors for PJI.